2019
DOI: 10.4103/ijo.ijo_2112_18
|View full text |Cite
|
Sign up to set email alerts
|

Observer-masked trial comparing efficacy of topical olopatadine (0.1%), bepotastine (1.5%), and alcaftadine (0.25%) in mild to moderate allergic conjunctivitis

Abstract: Purpose: With increasing environmental pollution, the incidence of allergic conjunctivitis is increasing. Newer anti-allergic medications with combined anti-histaminic and mast cell stabilization action can help reducing the use of topical steroids for milder form of disease. There is no study directly comparing olopatadine (0.1%), bepotastine (1.5%), and alcaftadine (0.25%) for mild to moderate allergic conjunctivitis cases. Hence, we decided to methodically study the efficacy of three topical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…A comparative study done by Dudeja I, et al concluded Alcaftadine 0.25%, olopatadine 0.2%, and bepotastine 1.5% eye drops have been proved to be safe and well-tolerated topical medication for allergic conjunctivitis. [ 9 ] This study resounded the same, and the medications were found to be safe, with minimal transient side effects of burning sensation and taste impairment noticed by a few patients (more in group 1 and group 3, respectively). Most patients responded to treatment and were willing to continue the eye drop, if indicated.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…A comparative study done by Dudeja I, et al concluded Alcaftadine 0.25%, olopatadine 0.2%, and bepotastine 1.5% eye drops have been proved to be safe and well-tolerated topical medication for allergic conjunctivitis. [ 9 ] This study resounded the same, and the medications were found to be safe, with minimal transient side effects of burning sensation and taste impairment noticed by a few patients (more in group 1 and group 3, respectively). Most patients responded to treatment and were willing to continue the eye drop, if indicated.…”
Section: Discussionmentioning
confidence: 54%
“…Total Ocular Symptom Scoring System (TOSS) scoring was used to grade the signs and symptoms. All patients aged between 18 and 60 years belonging to either gender, with mild-to-moderate allergic conjunctivitis [ Table 1 ][ 9 ] presenting to outpatient department between July 2019 and September 2019 were included after obtaining written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 24 ] Bepotastine is a less commonly used drug. [ 25 26 ] In this review, we seek to assess the two medications and evaluate their effectiveness in treating Spring Catarrh. For this study, different signs and symptoms of VKC were used as criteria for assessment.…”
Section: Discussionmentioning
confidence: 99%
“…1st, 3rd, and 6th month signs’ of the participants were evaluated from medical records. The four signs, papillary reaction, limbal involvement, corneal involvement, and conjunctival hyperemia were graded using the 4-point system (0, none; 1, mild; 2, moderate; and 3 severe) as defined by Uchio et al [ 15 ] and similar to the system used in the study by Dudeja et al [ 16 ]; and the groups were compared using this scoring system. The upper and lower extreme scores were as follows: for upper tarsal papillae, 0 indicates no papillae and 3 indicates predominance of Giant papillae; for limbal activity, 0 indicates no activity and 3 indicates the presence of Horner-Trantas dots; for corneal involvement, 0 indicates intact corneal epithelium and 3 indicates diffuse punctate keratopathy; for conjunctival hyperemia, 0 indicates absence of dilated blood vessels in conjunctiva and 3 indicates generalized dilation of blood vessels.…”
Section: Methodsmentioning
confidence: 99%